2017
DOI: 10.1371/journal.pone.0181667
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cross talk between ER stress and inflammation in age-related macular degeneration

Abstract: Increasing evidence demonstrates that inflammation and endoplasmic reticulum (ER) stress is implicated in the development and progression of age-related macular degeneration (AMD), a multifactorial neurodegenerative disease. However the cross talk between these cellular mechanisms has not been clearly and fully understood. The present study investigates a possible intersection between ER stress and inflammation in AMD. In this study, we recruited two collections of involved protein markers to retrieve their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 79 publications
1
10
0
1
Order By: Relevance
“…In acute injuries, inflammation restores tissue homeostasis but prolonged inflammatory conditions stimulate the immunosuppressive network in an attempt to prevent excessive inflammatory damage in tissues (see below). There is clear evidence that ER stress can elicit inflammatory responses in many age-related diseases, e.g., atherosclerosis [72], hepatic steatosis [73], and age-related macular degeneration [74]. It seems that the activation of inflammasomes is involved in the crosstalk between ER stress and inflammatory responses in some diseases [72,73].…”
Section: Er Stress Is a Potent Inducer Of Inflammationmentioning
confidence: 99%
“…In acute injuries, inflammation restores tissue homeostasis but prolonged inflammatory conditions stimulate the immunosuppressive network in an attempt to prevent excessive inflammatory damage in tissues (see below). There is clear evidence that ER stress can elicit inflammatory responses in many age-related diseases, e.g., atherosclerosis [72], hepatic steatosis [73], and age-related macular degeneration [74]. It seems that the activation of inflammasomes is involved in the crosstalk between ER stress and inflammatory responses in some diseases [72,73].…”
Section: Er Stress Is a Potent Inducer Of Inflammationmentioning
confidence: 99%
“…In the process of protein folding, resident protein disulfide isomerases (PDI), endoplasmic reticulum oxidoreduction 1 (ERO1) and glutathione (GSH) cooperate as a chaperone-like assisted mechanism to prevent and correct aberrant disulfide bonds [ 15 ]. Previous studies have shown that excessive intracellular ROS may lead to depletion of the GSH pool and compromise the function of PDI, which disrupts the folding process of proteins in the ER and produces a massive amount of misfolded proteins [ 16 , 17 ]. However, the excessive accumulation of misfolded proteins in the ER may trigger an unfolded-protein response (UPR), which may enhance protein folding ability, as well as the homeostasis of protein translation and accelerate protein degradation to recover ER function [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hard-to-cure human diseases such as diabetes, cancer or neurodegenerative disorders are often multifactorial in nature implying that a diverse range of underlying mechanisms behind disease genesis and progression need to be taken into consideration for improved management. An important manifestation of the biological networks is shown by gene regulatory networks that provide functional explanations for many biological phenomena and pathological conditions by identifying key molecules, their relevant pathways, and their causative relationships [28]. BC heterogeneity that drives tumorigenesis, metastasis, recurrence, and drug resistance necessitates drugs combinatory and multi-target strategies to be halted.…”
Section: Discussionmentioning
confidence: 99%